Predictors of long-term cancer-related distress among female BRCA1 and BRCA2 mutation carriers without a cancer diagnosis: an international analysis - Metcalfe, Kelly A. (Br J Cancer, 2020)
BACKGROUND: Women with a BRCA1 or BRCA2 mutation have high lifetime risks of developing breast and ovarian cancers. We sought to estimate the prevalence of cancer-related distress and to identify predictors of distress in an international sample of unaffected women with a BRCA mutation. METHODS: Women with a BRCA1/2 mutation and no previous cancer diagnosis were recruited from the United States, Canada, the United Kingdom, Australia and from a national advocacy group. Using an online survey, we asked about cancer risk reduction options and screening, and we measured cancer-related distress using the Impact of Event Scale. RESULTS: Among 576 respondents, mean age was 40.8 years (SD = 8.1). On average 4.9 years after a positive test result, 16.3% of women reported moderate-to-severe cancer-related distress. Women who had undergone risk-reducing breast and ovarian surgery were less likely to have (moderate or severe) cancer-related distress compared to other women (22.0% versus 11.4%, P value = 0.007). Women recruited from the advocacy group were more likely to have cancer-related distress than other women (21.6% versus 5.3%, P value = 0.002). CONCLUSIONS: Approximately 16% of women with a BRCA1 or BRCA2 mutation experience distress levels comparable to those of women after a cancer diagnosis. Distress was lower for women who had risk-reducing surgery.